A Bottom-Up Approach to the Risk-Adjusted Performance of the Buyout Fund Market. Issue 4 (1st July 2016) - L'Her, Jean-François; Stoyanova, Rossitsa; Shaw, Kathryn; Scott, William; Lai, Charissa
Abstract : We use the Burgiss dataset to study private equity buyout fund performance. Our findings on performance before risk adjustments are consistent with those in the literature and indicate significant outperformance of buyout fund investments. Using a bottom-up approach, we identify the systematic risks of underlying companies in buyout funds to inform an appropriate risk-adjusted benchmark, which we determine to be a levered size- and sector-adjusted public index. After making these risk adjustments, we find no significant outperformance of buyout fund investments versus the public market equivalent on a dollar-weighted basis. We contend that even without significant risk-adjusted outperformance, buyout funds can play a valuable role in institutional investors' portfolios. Abstract : Editor's note: This article was reviewed and accepted by Robert Litterman, executive editor at the time the article was submitted. Authors' note: Because this article was prepared by the authors in their personal rather than organizational capacities, the views expressed in this article are those of the authors alone and do not necessarily reflect the positions of either the Abu Dhabi Investment Authority (ADIA) or the Canada Pension Plan Investment Board (CPPIB) nor their policies and practices. Although the authors have taken every care to ensure that the information contained in this article is true and correct at the time of publication, neither the authors, the ADIA, nor the CPPIB make any representation or warranty with respect to the accuracy or completeness of this article.